Resource-efficient numerical computing and elastic wave behavior analysis in complex poroelastic media - Zhitao Zhang; Yuhang Guo; Zhuwen Wang; Baozhi Pan; Yibo Wang; Lin Gan; Wubing Wan; Zhaoqi Sun; Wenqiang Wang; Ruiyi Han; Jiaxu Guo; Yitong Cui (Computers and Geotechnics, 2026)

HDAC5 mediates the regulation of muscle-derived interleukin 6 on the differentiation of porcine intramuscular pre-adipocytes - Weimin Lin; Hongbing Song; Chongfan Du; Jing Wang; Xiaohan Zhang; Chu Yang; Tianfang Xiao; Ruiyi Lin (Domestic Animal Endocrinology, 2026)

Maternal Genetic Diversity Analysis of Guanling Cattle by Mitochondrial Genome Sequencing - Longxin Xu; Xin Wang; Hua Wang; Junda Wu; Wenzhang Zhou; Mengmeng Ni; Kaikai Zhang; Yuanfeng Zhao; Ruiyi Lin (Biochemical Genetics, 2025)

Artificial intelligence for calculating and predicting building carbon emissions: a review - Jianmin Hua; Ruiyi Wang; Ying Hu; Zimeng Chen; Lin Chen; Ahmed I. Osman; Mohamed Farghali; Lepeng Huang; Ji Feng; Jun Wang; Xiang Zhang; Xingyang Zhou; et al. (Environmental Chemistry Letters, 2025)
The construction industry, being responsible for a large share of global carbon emissions, needs to reduce its high carbon output to meet carbon reduction goals. Artificial intelligence can provide efficient support for carbon emission calculation and prediction. Here, we review the use of artificial intelligence techniques in forecasting, management and real-time monitoring of carbon emissions, focusing on how they are applied, their impacts, and challenges. Compared to traditional methods, the prediction accuracy of artificial intelligence models has increased by 20%. Artificial intelligence-driven systems could reduce carbon emissions by up to 15% through real-time monitoring and adaptive management strategies. Artificial intelligence applications improve energy efficiency in buildings by up to 25%, while reducing operational costs by up to 10%. Artificial intelligence supports the establishment of a digital carbon management system and contributes to the development of the carbon trading market.

Dissolved oxygen activated by single-atom-state iron coupled with sodium dithionite for norfloxacin degradation: Efficiency and mechanism - Wei Song; Sen Xu; Caixia Fu; Ruiyi Huang; Hongze Fang; Li Li; Dachao Lin; Yuning Fang; Xing Du; Zhihong Wang (Journal of Cleaner Production, 2025)

Green building practices to integrate renewable energy in the construction sector: a review - Lin Chen; Ying Hu; Ruiyi Wang; Xiang Li; Zhonghao Chen; Jianmin Hua; Ahmed I. Osman; Mohamed Farghali; Lepeng Huang; Jingjing Li; Liang Dong; David W. Rooney; et al. (Environmental Chemistry Letters, 2024)
The building sector is significantly contributing to climate change, pollution, and energy crises, thus requiring a rapid shift to more sustainable construction practices. Here, we review the emerging practices of integrating renewable energies in the construction sector, with a focus on energy types, policies, innovations, and perspectives. The energy sources include solar, wind, geothermal, and biomass fuels. Case studies in Seattle, USA, and Manama, Bahrain, are presented. Perspectives comprise self-sufficiency, microgrids, carbon neutrality, intelligent buildings, cost reduction, energy storage, policy support, and market recognition. Incorporating wind energy into buildings can fulfill about 15% of a building's energy requirements, while solar energy integration can elevate the renewable contribution to 83%. Financial incentives, such as a 30% subsidy for the adoption of renewable technologies, augment the appeal of these innovations.

Dual-targeting lanthanide-ICG-MOF nanoplatform for cancer Theranostics: NIR II luminescence imaging guided sentinel lymph nodes surgical navigation - Bi Lin; Ruiyi Dai; Zhenghao Liu; Wenjing Li; Jingwen Bai; Guojun Zhang; Ruichan Lv (Journal of Photochemistry and Photobiology B: Biology, 2023)

The Effects of Limosilactobacillus reuteri LR-99 Supplementation on Body Mass Index, Social Communication, Fine Motor Function, and Gut Microbiome Composition in Individuals with Prader–Willi Syndrome: a Randomized Double-Blinded Placebo-Controlled Trial - Xue-Jun Kong; Kevin Liu; Patrick Zhuang; Ruiyi Tian; Siyu Liu; Cullen Clairmont; Xiaojing Lin; Hannah Sherman; Junli Zhu; Yelan Wang; Michelle Fong; Alice Li; et al. (Probiotics and Antimicrobial Proteins, 2021)
Prader–Willi syndrome (PWS) is a rare genetic disorder associated with developmental delay, obesity, and neuropsychiatric comorbidities. Limosilactobacillus reuteri ( Lactobacillus reuteri , Lact. reuteri ) has demonstrated anti-obesity and anti-inflammatory effects in previous studies. In the present study, we aim to evaluate the effects of Lact. reuteri supplementation on body mass index (BMI), social behaviors, and gut microbiota in individuals with PWS. We conducted a 12-week, randomized, double-blind, placebo-controlled trial in 71 individuals with PWS aged 6 to 264 months (64.4 ± 51.0 months). Participants were randomly assigned to either receive daily Lact. reuteri LR-99 probiotic (6 × 10 10 colony forming units) or a placebo sachet. Groupwise differences were assessed for BMI, ASQ-3, and GARS-3 at baseline, 6 weeks, and 12 weeks into treatment. Gut microbiome data was analyzed with the QIIME2 software package, and predictive functional profiling was conducted with PICRUSt-2. We found a significant reduction in BMI for the probiotic group at both 6 weeks and 12 weeks relative to the baseline ( P < 0.05). Furthermore, we observed a significant improvement in social communication and interaction, fine motor function, and total ASQ-3 score in the probiotics group compared to the placebo group ( P < 0.05). Altered gut microbiota was observed in the probiotic group to favor weight loss and improve gut health. The findings suggest a novel therapeutic potential for Lact. reuteri LR-99 probiotic to modulate BMI, social behaviors, and gut microbiota in Prader–Willi syndrome patients, although further investigation is warranted. Trial registration Chinese Clinical Trial Registry: ChiCTR1900022646